KARAKTERISTIK LAGU YANG SESUAI UNTUK ANAK DITINJAU DARI SEGI AMBITUS - Rina Wulandari (MAJALAH ILMIAH PEMBELAJARAN, 2008)
Music vocal at education institute have many problems inconsiderable song study. ambitus is one of solutions where ateacher can plan song activities for kids better with thisreferences; first, a teacher must have music manuscript in hislesson plan. It would be better in music notation. Second, ateachers must identify low and high tones from the song, andthen compare it with children ambitus. It must not lower than“a” and not higher than “f”.